Phenobarbital does not worsen outcomes of neonatal hypoxia on hippocampal LTP on rats - Sanchez-Brualla, Irene; Ghosh, Anjik; Gibatova, Viktoriya A.; Quinlan, Sean; Witherspoon, Eric; Vicini, Stefano; Forcelli, Patrick A. (Frontiers in Neurology, 2023)
Introduction Neonatal hypoxia is a common cause of early-life seizures. Both hypoxia-induced seizures (HS), and the drugs used to treat them (e.g., phenobarbital, PB), have been reported to have long-lasting impacts on brain development. For example, in neonatal rodents, HS reduces hippocampal long-term potentiation (LTP), while PB exposure disrupts GABAergic synaptic maturation in the hippocampus. Prior studies have examined the impact of HS and drug treatment separately, but in the clinic, PB is unlikely to be given to neonates without seizures, and neonates with seizures are very likely to receive PB. To address this gap, we assessed the combined and separate impacts of neonatal HS and PB treatment on the development of hippocampal LTP. Methods Male and female postnatal day (P)7 rat pups were subjected to graded global hypoxia (or normoxia as a control) and treated with either PB (or vehicle as a control). On P13-14 (P13+) or P29-37 (P29+), we recorded LTP of the Schaffer collaterals into CA1 pyramidal layer in acute hippocampal slices. We compared responses to theta burst stimulation (TBS) and tetanization induction protocols. Results Under the TBS induction protocol, female rats showed an LTP impairment caused by HS, which appeared only at P29+. This impairment was delayed compared to male rats. While LTP in HS males was impaired at P13+, it normalized by P29+. Under the tetanization protocol, hypoxia produced larger LTP in males compared to female rats. PB injection, under TBS, did not exacerbate the effects of hypoxia. However, with the tetanization protocol, PB – on the background of HS – compensated for these effects, returning LTP to control levels. Discussion These results point to different susceptibility to hypoxia as a function of sex and age, and a non-detrimental effect of PB when administered after hypoxic seizures.